2012
DOI: 10.1603/ec11121
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Dendroctonus brevicomis (Coleoptera: Curculionidae) in Behavioral Assays: Implications to Development of a Semiochemical-Based Tool for Tree Protection

Abstract: Currently, techniques for managing western pine beetle, Dendroctonus brevicomis LeConte (Coleoptera: Curculionidae, Scolytinae), infestations are limited to tree removals (thinning) that reduce stand density and presumably host susceptibility, and/or the use of insecticides to protect individual trees. There continues to be significant interest in developing an effective semiochemical-based tool for protecting trees from D. brevicomis attack, largely as an alternative to conventional insecticides. The response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…There is an accumulating body of evidence suggesting that foraging coniferophagous bark beetles detect and avoid volatile compounds released from the leaves and/or bark of angiosperms and other nonhost taxa ('nonhost volatiles'), and thereby may improve foraging efficiency by avoiding nonhostdominated habitats and landings on unsuitable trees. Numerous individual nonhost volatiles have been identified and shown to inhibit coniferophagous bark beetle responses to traps baited with attractant pheromones and/or host kairomones (e.g., Dickens et al, 1992;Huber and Borden, 2003;summarized in Zhang and Schlyter, 2004;Zhang et al, 2007;Dodds and Miller, 2010;Fettig et al, 2012). Furthermore, nonhost volatiles have been used with some success to protect individual trees from bark beetle attacks Jakuš et al, 2003;Fettig et al, 2009;Schiebe et al, 2011;Schlyter, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is an accumulating body of evidence suggesting that foraging coniferophagous bark beetles detect and avoid volatile compounds released from the leaves and/or bark of angiosperms and other nonhost taxa ('nonhost volatiles'), and thereby may improve foraging efficiency by avoiding nonhostdominated habitats and landings on unsuitable trees. Numerous individual nonhost volatiles have been identified and shown to inhibit coniferophagous bark beetle responses to traps baited with attractant pheromones and/or host kairomones (e.g., Dickens et al, 1992;Huber and Borden, 2003;summarized in Zhang and Schlyter, 2004;Zhang et al, 2007;Dodds and Miller, 2010;Fettig et al, 2012). Furthermore, nonhost volatiles have been used with some success to protect individual trees from bark beetle attacks Jakuš et al, 2003;Fettig et al, 2009;Schiebe et al, 2011;Schlyter, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Under IPM, semiochemicals are used to monitor pest populations as well as for mass trapping and mating disruption (Campion et al, 1985). Examples of semiochemicals for pest control have been reported by various authors, including the development of semiochemical-based tools to protect trees from bark beetle infestations using mainly antiaggregation and aggregation pheromones (Fettig et al, 2012). Gillette et al (2009) indicated that the objective is to attract, retain and later destroy the pest.…”
Section: Discussionmentioning
confidence: 99%
“…The effect was conÞrmed in several additional studies (Fettig et al 2009b). Fettig et al (2012) reported a revised Þve-component blend [nonanal, (E)-2-hexenal, (E)-2-hexen-1-ol, (Z)-2-hexen-1-ol, and (Ð)-verbenone; RB] signiÞcantly reduced D. brevicomis attraction by 73.1% compared with attractant-baited traps (Fettig et al 2012). In experiment 1, RB ϩ WPB had no effect on the density of D. brevicomis attacks on attractant-baited trees (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, initial blends were complex and likely not feasible for operational use. Fettig et al (2012) further examined the response of D. brevicomis to several blends of nonhost angiosperm volatiles and (Ð)-verbenone in attractantbaited traps in hopes of improving the efÞcacy of their nine-component blend and reducing the number of components involved. They documented the inhibitory effect of a revised Þve-component blend [nonanal, (E)-2-hexenal, (E)-2-hexen-1-ol, (Z)-2-hexen-1-ol, and (Ð)-verbenone], and later demonstrated that adding acetophenone (Erbilgin et al 2007(Erbilgin et al , 2008 to this blend allowed removal of the aldehydes [nonanal and (E)-2-hexenal] without compromising efÞcacy.…”
mentioning
confidence: 99%
See 1 more Smart Citation